Gambaran Post Operative Nausea and Vomiting Pada Pasien Sectio Caesarea Dengan Metode Enhanced Recovery Caesarean After Surgery Di RSUD Ajibarang - Widiyastuti, Widiyastuti; Sebayang, Septian Mixrova; Hikmanti, Arlyana (Yayasan Jompa Research and Development, 2025)
Caesarean delivery has complications, one of which is Post Operative Nausea and Vomiting (PONV). Over time, new methods have been applied to reduce PONV complications, using the Enhanced Recovery After Caesarean Surgery (ERACS) method. This study aims to describe the occurrence of Post Operative Nausea and Vomiting (PONV) in patients undergoing Caesarean Section (CS) delivery at Ajibarang Regional General Hospital. The research design is a descriptive study with a cross-sectional approach, involving 83 patients selected by purposive sampling according to inclusion criteria. The research instrument used the RINVR observation sheet, and data were collected from primary and secondary sources, then analyzed univariately. The results showed that the majority of patients were aged 26-35 years (45.8%), had no history of PONV or motion sickness (69.9%), fasted less than 6 hours (91.6%), and most patients underwent surgery lasting 1 hour (62.7%). Additionally, most patients experienced PONV symptoms that were mild (10.8%), with no moderate, severe, or very severe symptoms found. This study concludes that the application of the ERACS method at Ajibarang Regional General Hospital is proven effective in minimizing the incidence and severity of PONV in CS patients, with most patients experiencing no PONV or only mild symptoms (10.8%).